THE ROLE OF THE DIGITAL ECONOMY IN INCREASING PUBLIC INTEREST IN SHARIA MUTUAL FUND INVESTMENT THROUGH E-COMMERCE PLATFORMS - Septiani, Dila; Sihombing, Dwy Arnanda; Hamdani, Muhammad Fadhil; Elfikri, Muhammad Fawaz; Hafiz, Muhammad; Britania, Yolanda (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to determine the level of investment in sharia mutual funds to attract public interest in Indonesia through digital economic media such as e-commerce. Currently, sharia investment in Indonesia is less desirable, especially in the sharia mutual fund sector. Judging from the economic development, conventional mutual fund investment activities dominate. Then through the digital economy, business development or trade transactions that utilize digital media as a means of communication, collaboration and economic activities between companies or between individuals such as e-business and e-commerce continue to increase. The method used in this study is a qualitative research method, namely by using a literature review by taking references from several e-books and journals obtained from website or internet sources. The results showed that the digital economy through e-commerce in Indonesia has many positive impacts, but at the level of stock investment Islamic mutual funds are still less attractive to the public compared to conventional mutual funds.